Factors Affecting Employee Engagement Mediated by Practices and Workplace Happiness in Private Companies - Gulo, Alfin Kristian; Berliyanti, Dita Oki; Nilasari, B. Medina (Jurnal Ilmiah Manajemen dan Bisnis, 2025)
This study aims to analyze the effect of Sustainable Human Resource Management (SHRM) and Drivers of Employee Engagement on Employee Engagement, with Practices and Workplace Happiness as mediating variables. This research was conducted in private companies in the Jabodetabek area. Data was collected from 141 respondents using a questionnaire and analyzed using the Smart PLS Method. The results showed that SHRM has a positive and significant effect on Practices and Workplace Happiness, and Practices and Workplace Happiness have a positive and significant effect on Employee Engagement. In addition, Drivers of Employee Engagement also has a positive and significant influence on Employee Engagement. These findings indicate the importance of combining sustainable HR practices and a happy work environment to optimize employee engagement.